Comparing the Treatment Outcomes of Absorbable Sutures, Nonabsorbable Sutures, and Tissue Adhesives in Cleft Lip Repair: A Systematic Review. (January 2022) - Egbunah, Uchenna P.; Adamson, Olawale; Fashina, Azeez; Adekunle, Adegbayi A.; James, Olutayo; Adeyemo, Wasiu L.
Objectives: To examine the literature and synthesize the available reports for the best possible option between absorbable, nonabsorbable, and tissue adhesives in cleft lip skin closure. Design: We conducted systematic searches for randomized controlled trials and controlled clinical trials in PubMed, Cochrane, Ovid Medline, and OpenGrey databases. Identified studies were retrieved and assessed for eligibility. All statistical analyses were done with Revman, version 5.4. Interventions: The intervention considered in this systematic review were techniques of cleft lip repair using resorbable sutures, nonabsorbable sutures, medical adhesives, or any combination of these. Outcome Measures: The primary outcomes assessed in the trials had to include any combination of the following: wound healing cosmesis and wound healing complications. While secondary outcomes considered were quality of life, direct and indirect costs to patients and health services, and participant satisfaction. Results: Only 6 studies met all inclusion criteria and were selected for qualitative analysis. A more favorable wound healing cosmesis was seen when nonabsorbable suture was used in cleft lip repair compared to absorbable sutures and tissue adhesives (CI, 0.65-4.35). This advantage was overshadowed by the significantly higher prevalence of postoperative complications when nonabsorbable sutures are used. Conclusion: Although the results point to more favorable cosmesis with nonabsorbable sutures and an overall more favorable outcome with either absorbable sutures or tissue adhesives, the 6 selected studies were assessed at an unclear risk of bias; therefore, the results of this study should be interpreted with caution and regarded as low-certainty evidence.